2022
DOI: 10.1038/s41598-022-22797-7
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning diagnostics for bladder tumor identification and grade prediction using RGB method

Abstract: We evaluate the diagnostic performance of deep learning artificial intelligence (AI) for bladder cancer, which used white-light images (WLIs) and narrow-band images, and tumor grade prediction of AI based on tumor color using the red/green/blue (RGB) method. This retrospective study analyzed 10,991 cystoscopic images of suspicious bladder tumors using a mask region-based convolutional neural network with a ResNeXt-101-32 × 8d-FPN backbone. The diagnostic performance of AI was evaluated by calculating sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Shkolyar et al examined only CIS and reported at the AUA2023 [15]. In addition to white light imaging, narrow band imaging, Photodynamic diagnosis using blue light imaging has been reported [7,15,16]. Yoo et al focused on the three primary colours of light: red, green, and blue [7].…”
Section: Resultsmentioning
confidence: 99%
“…Shkolyar et al examined only CIS and reported at the AUA2023 [15]. In addition to white light imaging, narrow band imaging, Photodynamic diagnosis using blue light imaging has been reported [7,15,16]. Yoo et al focused on the three primary colours of light: red, green, and blue [7].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas other studies evaluated their models on a select set of frames, our validation set captures the entirety of the diagnostic portion of TURBT videos. While prior studies focused on either the detection of cancerous bladder tumors or the detection of specific bladder tumor morphologies [9,10,29], we developed and evaluated a series of sequential models on a dataset containing bladder cancer of varying stages, grades, and appearances. We also included pathology-confirmed benign lesions in the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…The 92.91% Dice score achieved by our PAN model indicates better tumor localization ability than reported in previous studies. As listed in Section 1 , the attention mechanism-based U-Net of Zhang et al [ 19 ] achieved a Dice score of 82.5%, the mask region-based CNN of Yoo et al [ 6 ] obtained a score of 74.7%, while the CystoNet of Shkolyar et al [ 4 ] did not report the Dice score result, but their per-frame sensitivity of 90.9% is lower than the 94.79% of our PAN model. This improvement in accuracy may be the result of more appropriate pre-processing of the input image, a better choice of neural network architecture, or a difference in the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning (DL) methods are developing rapidly, and as a result, neural network-based bladder cancer diagnosis is becoming increasingly popular [ 4 , 5 , 6 ]. DL solutions can not only achieve diagnostic accuracy similar to that of experienced specialists [ 2 , 7 ], but their results are also objective and reproducible [ 3 ], as they are based on mathematical operations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation